2010
DOI: 10.1177/0363546510361952
|View full text |Cite
|
Sign up to set email alerts
|

A Long-Term, Prospective, Randomized Study Comparing Biodegradable and Metal Interference Screws in Anterior Cruciate Ligament Reconstruction Surgery

Abstract: There were significantly larger radiographically visible bone tunnels on the femoral side but not on the tibial side in the PLLA group compared with the metal group 8 years after anterior cruciate ligament reconstruction using hamstring tendon autografts. This finding did not correlate with inferior clinical results. Because of the results in the present study, the authors have discontinued the use of PLLA interference screws.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 47 publications
1
53
0
4
Order By: Relevance
“…Many studies have compared fixation methods in ACLR. Some have demonstrated increased tunnel widening on the femoral side for bioabsorbable compared with metal screws 25,32,34,46 but without a difference in clinical outcomes at up to 2 years of follow-up. 12,15,21 We found no difference in the risk of revision ACLR with the available comparisons: suspensory button and staple, screws, biodegradable device, or a combination of implants (more than one of suspensory button, staple, screw), in keeping with previous findings but, more important, extending the follow-up out to 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have compared fixation methods in ACLR. Some have demonstrated increased tunnel widening on the femoral side for bioabsorbable compared with metal screws 25,32,34,46 but without a difference in clinical outcomes at up to 2 years of follow-up. 12,15,21 We found no difference in the risk of revision ACLR with the available comparisons: suspensory button and staple, screws, biodegradable device, or a combination of implants (more than one of suspensory button, staple, screw), in keeping with previous findings but, more important, extending the follow-up out to 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Metal interference screws designed by Kurosaka have been used as the standard fixation device in ACL reconstruction with patellar tendon autograft48). However, with the increasing use of hamstring soft tissue grafts, bioabsorbable interference screws, poly-L-lactic acid (PLLA) screws, and polyglyconate screws49) are becoming more popular. While the bioabsorbable screw has the advantages, such as incorporation into the surrounding tissue, almost no need for implant removal, and less interference with MRI50), it seems to provide clinical results similar to those of metal screws according to a systematic review.…”
Section: Fixation Devices For Acl Reconstructionmentioning
confidence: 99%
“…Although EndoButton has a higher failure load and less stiffness than interference screws, it induces some micro motion of the graft within the bone tunnel during loading, and can be a cause of tunnel widening49). Baumfeld et al54) reported that 2 cross pin fixation resulted in less femoral tunnel widening than the EndoButton fixation.…”
Section: Fixation Devices For Acl Reconstructionmentioning
confidence: 99%
“…1,7,8 While anterior knee laxity appears unaffected by tibial tunnel enlargement in the short term, the long-term relationship of tunnel enlargement with knee laxity and increased ACL failure is unknown. 1 This report demonstrates a case of severe tunnel enlargement after ACL revision with allograft and bioabsorbable screw fixation.…”
Section: Discussionmentioning
confidence: 99%